Interleukin-1β Level Is Increased in Vitreous of Patients with Neovascular Age-Related Macular Degeneration (nAMD) and Polypoidal Choroidal Vasculopathy (PCV) - Zhao, Min; Bai, Yujing; Xie, Wankun; Shi, Xuan; Li, Fangting; Yang, Fei; Sun, Yaoyao; Huang, Lvzhen; Li, Xiaoxin (PloS one, 2015)
To examine the expression of pro-interleukin-1β (pro-IL-1β) and interleukin-1β (IL-1β) in the vitreous body of patients with neovascular age-related macular degeneration(nAMD), polypoidal choroidal vasculopathy (PCV), proliferative diabetic retinopathy (PDR), retinal vein occlusion (RVO) or Eales' disease to further elucidate the role of IL-1β and inflammation in the pathogenesis of neovascular retinal disease. Prospective clinical laboratory investigation study. All patients enrolled had vitreous hemorrhage due to nAMD, PCV, PDR, RVO or Eales' disease that required vitrectomy. Patients were excluded for any history of active intraocular inflammation, or other ophthalmic surgery besides vitrectomy. Control samples were obtained from patients with idiopathic macular epiretinal membrane. A total of fifty vitreous samples were collected from patient during vitrectomy. Pro-IL-1β and IL-1β expression were measured by enzyme-linked immunosorbent assay (ELISA). Results were analyzed statistically using nonparametric tests. Expression of pro-IL-1β protein was increased by 2.83-fold and 9.19-fold in PCV and nAMD vitreous samples relative to control, respectively. Expression of IL-β protein was increased by 10-fold and 4.83-fold in PCV and nAMD vitreous samples relative to control, respectively. Our results demonstrate that expression of pro-IL-1β and IL-1β proteins is higher in PCV and nAMD. The roles of pro-IL-1β and IL-1β as inflammatory mediators in the development of PCV and nAMD may be associated with photoreceptor degeneration and neovascularization which necessitates further study.